Z-sep+ based QuEChERS technique for the pre-concentration of malathion pesticide in fruits followed by analysis using UV-Vis spectroscopy. Issue 12 (1st December 2020) - Musarurwa, Herbert; Chimuka, Luke; Tavengwa, Nikita T.
ABSTRACT: In this work, the concentrations of malathion in fruits were determined using UV-Vis spectrophotometry prior to pre-concentration using QuEChERS. The Z-sep + /PSA sorbent combination was used for the d-SPE clean-up and extraction was done using acetonitrile during QuEChERS. The absorbance of malathion was measured using a UV-Vis spectrophotometer at a wavelength of 415 nm. The QuEChERS parameters, which included type and volume of extraction solvent, type and mass of sorbents, and centrifugation rate, were optimised prior to application of the developed method to real fruit samples. The linear range was from 0.1 to 0.9 mg kg −1 while the coefficient of determination (R 2 ) was 0.9999. The limit of detection (LOD) for malathion was found to be 0.017 mg kg −1 and the limit of quantification was 0.05 mg kg −1 . Orange samples were found to have no malathion residues when the developed method was applied to them while the concentrations of malathion in apple and pear samples were 0.07 mg kg −1 and 0.09 mg kg −1 respectively.